Os altos empregados e a subordinação jurídica gerencial - Conceição, Luan Pedro Lima da (2024)
While facing a scenario of significant changes in labor conditions from recent technological, social, and economic advances, Labor Law has been undergoing challenging reforms. Among the major innovations are issues related to high-racking employees, hyper-sufficient employees, and self-employees, stand out a true frontier for Labor Law. Considering this, this thesis emerges as an attempt to reflect and analyze the widely spread discourses defending that the legal subordination of highracking employees is light or reasonable. During the research development, the egalitarian liberalism of John Rawls provides the philosophical foundation to justify state regulation of individual labor relations, attributing to Labor Law the function of realizing the minimum living spences, also possessing redistributive characteristics. Subsequently, Labor Law was established as a fundamental mechanism for balancing values, adopting an ideal of interpretation in which the interpreter, drawing on the central principles and values of this branch of law, constructs meanings and interpretations from labor norms, so that the conceptualization of high-racking employees as professionals in the highest positions within organizational structures, leads to the conclusion that they are subject to legal subordination with new characteristics, especially the partial transfer of business risk to the employee, as well as intense integration into the corporate or business structure, representing a new dimension of legal subordination, managerial subordination. Therefore, we can verify that Labor Law, based on established theoretical frameworks, allows for the possibility of expanding the concept of legal subordination